Perilaku Ibu pada Pemberian Makanan Pendamping ASI (MPASI) di Kelurahan Pegirian - Santi Lestiarini; Yuly Sulistyorini (Jurnal Promkes: The Indonesian Journal of Health Promotion and Health Education, 2020)
Background: The target of exclusive breastfeeding has not been achieved because complementary feeding (MPASI) has been given earlier. Infants aged 0-6 months should only get breastfed without any complementary food. Objective: This paper aimed to analyze factors related to maternal behavior towards complementary feeding (MPASI) in Pegirian Village. Method: This study was observational and cross-sectional, involving all mothers and caregivers of under-five-year-old children in Pegirian Village. The sample size was 35 mothers and caregivers of toddlers in Neighborhood Association No. 06 Community Association 02 Pegirian Village, Surabaya City. Sampling technique in use was saturated sampling or census method because the total population was less than 100. The research variables included educational background, income, and actions in giving MPASI. Correlation test was in use to see the relationship among factors. Results: The results showed that there was a relationship between knowledge and attitude with complementary feeding behavior (P value = 0.001 and 0.015). There was no relationship between the level of education and employment status with complementary feeding behavior towards infants aged less than 6 months (P values = 0.425 and 0.134). Conclusion: Knowledge and attitude of mothers and caregivers can influence complementary feeding for infants aged less than 6 months.